2016
DOI: 10.1097/dcr.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Outcome of Robot-assisted and Open IPAA

Abstract: In this implementation phase, robot-assisted IPAA surgery offers acceptable short-term outcomes. The limitations of this observational study call for randomized controlled trials with long-term follow-up and exploration of functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 29 publications
(18 reference statements)
5
42
1
Order By: Relevance
“…There is promise, however, in the low short-term postoperative morbidity after minimally invasive surgery. Mark-Christensen et al reported that the readmission rate was higher in those who had robotic IPAA compared to open (40% vs 26%); however, the length of hospital stay was significantly shorter [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is promise, however, in the low short-term postoperative morbidity after minimally invasive surgery. Mark-Christensen et al reported that the readmission rate was higher in those who had robotic IPAA compared to open (40% vs 26%); however, the length of hospital stay was significantly shorter [6].…”
Section: Discussionmentioning
confidence: 99%
“…Schiessling et al evaluated the short-term outcomes of laparoscopic and open IPAA and have demonstrated no significant advantages for laparoscopy, except for cosmetic satisfaction. The conversion rate from laparoscopic to open approach was 23.8%, and the study appears to be underpowered due to the low number of patients [6,7]. Subsequently, Benlice et al demonstrated that when IPAA is done laparoscopically the incidence of incisional hernia is not diminished compared to an open group (8.4% vs 5.9%; P = 0.40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…colectomy ± lap. double-stapled IPAA + end ileostomy 4 robotic arms (camera port at the superior portion of umbilicus), assistant port in RUQ Single NR Period 1 293.2 ± 95.7 vs. Period 2 264.7 ± 93.6 Mark-Christensen et al [ 17 ] Aarhus, Denmark 2016 Jan. 2004–Sept. 2014 81 Control = 170 UC CMOR 5 Robotic completion proctectomy ± lap colectomy ( n = 2; the remaining 79 had previously undergone lap.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding colectomy only, the evidence for a laparoscopic approach is slightly stronger (see Section 4). Robot-assisted pouch procedures appear to offer acceptable short-term outcomes but there is no highquality evidence to suggest superior outcomes compared with existing techniques [350]. Similarly, SILS [351] and natural orifice specimen extraction techniques [352] have been described but require further investigation before recommendation.…”
Section: Laparoscopic Pouch Formation Robotics Sils and Natural Orimentioning
confidence: 99%